Forecasting number of breast cancer cases in Hospital Raja Perempuan Zainab II starting from january 2004 to december 2013 / Zulfatin Zakaria - Zakaria, Zulfatin (Bachelor of Science (Hons.) Statistics, 2015)
Breast cancer is the most common cancer among females. Breast cancer begins in the breast tissue that is made up of glands for milk production. This cancer typically detected either during a screening examination, before symptoms have developed, or after symptoms have developed, when woman feels a lump. Forecasting number of breast cancer cases in Hospital Raja Perempuan Zainab II starting from January 2004 to December 2013 was done by using data that are taken from medical record unit of the hospital. The aims of the study are to identify the component in the time series of number of breast cancer cases in Hospital Raja Perempuan Zainab II from January 2004 to December 2013, to determine the best model of the breast cancer cases, and to forecast the number of breast cancer cases for 2014. The methods that used in this study are Univariate Modeling Techniques and The Box-Jenkins Methodology. The results shown for Univariate Modeling Techniques, Single Exponential Smoothing is the best model since its Mean Squared Error (MSE) and Mean Absolute Percentage Error (MAPE) value was the lowest value compared to other method. Meanwhile, result of The Box-Jenkins Methodology shown the best model was ARIMA (1,1,2). This is because its value of MSE and MAPE gave the lowest value compared to other model. In conclusion, the univariate modeling technique which is single exponential smoothing is the best method for forecasting the number of breast cancer cases in Hospital Raja Perempuan Zainab II Kota Bharu. The forecast value for year 2014 shows the increase values of breast cancer cases than slowly decrease in a few months